Prevalencia de hematuria enzoótica bovina por medio de tiras reactivas en el cantón Las Lajas - Gallardo Ramírez, Luis Guillermo (2013)
This research was made in the canton Las Lajas, in 2013, in order to determine the prevalence of bovine enzootic hematuria, which was performed by using dipstick urinalysis. To make this work we investigated a total of 600 animals in 40 herds of Canton Las Lajas. Realize yourselves studies determined that the prevalence of bovine enzootic hematuria is 6.66%.